A influência do nano-recobrimento de cálcio e fósforo no processo de osteogênese in vitro - Moura, Camilla Christian Gomes (2009)
In vivo studies have reported that reduced dimensions bioactive ceramic coating overcomes the advantages of the PHSA. The aims of this study were to determine the effect of a uniform bioceramic coating in the nanothickness range onto a moderately rough surface on human harvested bone cells cultivated isolated or in coculture (osteogenic cells and PBMC). The cells were plated over titanium as-machined (S1) surfaces, alumina-blasted/acid etched surfaces (S2), and alumina-blasted/acid-etched + 300-500 nm thickness amorphous Ca e P based coating obtained by ion beam assisted deposition (S3) and evaluated regarding viability, adhesion, morphology, cytokines quantification (IL1, TGF1, IL17, IL10) and immunolocalization of osteopontin (OPN) and alkaline phosphatase (ALP). The results showed that the surface treatment did not interfere on cell viability of PBMC cell culture or osteogenic cells (p>0.005), though the adhesion of osteogenic cells have demonstrated a different pattern for each surface. At 1 day, S2 and S3 showed the betters results, showing greater adhesion than the S1surface (p<0.001). At 7 days the S1 surface showed a significantly higher adhesion than the S3 surface (p<0.005). The cell morphology evaluated on PBMC cultures showed spread morphology in S1 group. The osteogenic cells and the coculture showed a similar pattern for the tree surfaces in the evaluated times. However, when compared both cell cultures, coculture looked like less spread and smaller than osteogenic cells. The % of osteogenic cells showing intracellular label for OPN at day 1 was significantly higher for the S3 surface compared to the S1 surface (p<0.03), not showing differences in coculture. The % of ALP intracellular labeling at 7 days was significantly higher for the S2 surface compared to the S1 surface (p<0.0065), the same characteristic was observed on coculture (p<0,05). At 14 days, no differences in % ALP labeling was observed in osteogenic cells between the surfaces (p>0.09). However in coculture % ALP labeling was significantly higher for the S3 group compared to the S2 group (p<0.005). Regarding the cytokine levels were not observed a pattern for osteogenic cells, monocytes or coculture. The cytokine levels ranged among the three groups (S1, S2, S3) for each cell culture. Probably, cell interactions and cell surface contact have had an important effect on cytokine release. These results indicate that surface composition and texture influence the early events related to in vitro osteogenesis and that the cytokine production probably was modulated by cell interactions.